2016
DOI: 10.1111/pbr.12348
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic alteration of a thermo‐sensitive male sterility SP2S in rapeseed (Brassica napus) in response to mild temperature stress

Abstract: We conducted a proteomic comparison between thermo-sensitive genic male sterility (TGMS) SP2S and its near-isogenic line SP2F grown at 22°C. The proteomes at microsporocyte meiosis and uninucleate microspore stages were profiled using 2-dimensional gel electrophoresis. Twenty-five well-reproducible spots (10 spots at microsporocyte meiosis stage and 15 spots at uninucleate microspore stage) containing 28 proteins were successfully identified by MALDI-TOF/TOF mass spectrometry. An elongation factor EF-2 at micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In various protein separation methods, 2-DE is most promising and accepted as a separation method and an analytical approach because of its powerful separation ability. 166 For example, 2-DE was used to decipher the molecular networks regulating the salt stress in rapeseed. A salinity susceptible cultivar of rapeseed was subjected to different salt treatments and found that Na + content and proline concentration were enhanced in leaf.…”
Section: The Interplay Of Omics Approaches To Address Abiotic Stressesmentioning
confidence: 99%
“…In various protein separation methods, 2-DE is most promising and accepted as a separation method and an analytical approach because of its powerful separation ability. 166 For example, 2-DE was used to decipher the molecular networks regulating the salt stress in rapeseed. A salinity susceptible cultivar of rapeseed was subjected to different salt treatments and found that Na + content and proline concentration were enhanced in leaf.…”
Section: The Interplay Of Omics Approaches To Address Abiotic Stressesmentioning
confidence: 99%
“…Some structural abnormalities in SP2S were observed, including the premature breakdown of an extremely vacuolated tapetum and a delayed dissolution of the tetrad wall covering the microspore ( Yu et al, 2015 ). We attempted to find some molecular clues to the TGMS system using a proteomic comparison of the floral buds of SP2S with its near-isogenic line (NIL) SP2F, but we identified only 28 differentially accumulated peptides ( Zhang et al, 2016 ). Transcriptomic analysis of a physiological process may obtain additional information that differs from proteomic analysis due to the very high resolution of transcriptome profiling and a limited correspondence between the mRNA level and protein abundance ( Kubala et al, 2015 ).…”
mentioning
confidence: 99%